Peningkatan Ekonomi Masyarakat Melalui Optimalisasi Potensi Lokal di Kabupaten Muna, Sulawesi Tenggara - Sri Wahyuni; Nanik Hindariantiningsih; Nani Yuniar; Selamet Aku; Destika Sepang Arunglangi; Aulia Ramadhani Rahim; Jusri Lambe (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Abstract: This Thematic Community Service Program aims to improve the economy of the community in Bone-Bone Village, Muna Regency, Southeast Sulawesi, through optimizing local potential. The main problem is the lack of community knowledge for processing local plantation products, such as bananas, cassava, and coconuts, into products of economic value. The implementation method includes three stages: preparation (coordination with village officials and collection of materials), extension (presentation of local food diversification materials and processing technology), and practical training (production of products with the community). Eight main activities carried out include food processing (banana flour and brownies, cassava flour and brownies, antioxidant coconut oil, and young coconut isotonic drinks) and sustainable agriculture (plant pesticides, organic fertilizer from household waste, liquid organic fertilizer from rice washing water, and extension on soil fertility and conservation). The program results showed high community enthusiasm, with 20-30 participants per activity. The products were of good quality and received positive feedback when exhibited at the Muna Bersemarak Festival and during the Governor of Southeast Sulawesi's visit. The community successfully acquired new skills in local food processing and environmentally friendly agricultural practices. This program had a significant impact in empowering the community to utilize local potential as a sustainable MSME business opportunity. It was concluded that optimizing local potential through knowledge transfer and appropriate technology can be a catalyst for economic development in coastal communities based on local resources.